IMF Staff papers : Volume 19 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1972)
This paper incorporates the forward exchange market into a model of a small open economy under perfect capital mobility. It is shown that the degree to which the forward rate responds to movements in the spot exchange rate is important in determining the qualitative and quantitative impacts of monetary and fiscal policies. Additionally, the effect of exogenous disturbances both to the demand for money and to the capital and current accounts in the balance of payments is examined. The analysis is applied to three foreign exchange regimes: rigidly fixed, completely flexible, and dual-the last system being one in which the commercial exchange rate is fixed, and the financial exchange rate is flexible. The paper focuses attention on the effects of monetary and fiscal policies in a regime of flexible exchange rates under perfect capital mobility. The model can be interpreted to embody the case in which speculators hold uncertain expectations, which are reflected in a less than infinitely elastic demand for forward funds at a given expected future spot rate. A more complete analysis would also allow for the fact that the forward rate would be determined not only by the joint actions of pure arbitrageurs and pure speculators but also by uncovered arbitrage, by traders, and by the possibility of intervention by the monetary authorities.